Exploration and exploitation : organization's age and the nature of its innovative behavior - Häggman, Susanna (2015)
This study examines the relationship of an organization's age and its innovative activity. The innovative activity of an organization is discussed and examined through the concepts of exploration and exploitation, basing on the previous literature on organizational ambidexterity. Three hypotheses on the relationship of aging and the innovative behavior of an organization are formed based on the ambidexterity literature and the theories of the effect of aging on an organization. These hypotheses are tested with logistic regression analyses on a patent data set covering the modern biotechnology industry in Finland between 1973–2008. The results of the analyses show that age has a weak but significant effect on the nature of an organization's innovative behavior.